2020
DOI: 10.1097/ijg.0000000000001644
|View full text |Cite
|
Sign up to set email alerts
|

Micropulse Cyclophotocoagulation: A Multicenter Study of Efficacy, Safety, and Factors Associated With Increased Risk of Complications

Abstract: Précis: Micropulse cyclophotocoagulation (MPCP) lowered intraocular pressure (IOP) in the short-term but nearly half required additional intervention. Mydriasis was the most common complication (11%); 15% lost ≥3 Snellen lines of acuity; 11% had persistent complications at last follow-up. Purpose: The purpose of this study was to evaluate the efficacy and complications of MPCP in a large series of patients with all stages of glaucoma. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 17 publications
1
46
0
Order By: Relevance
“…This method could have lead to cyclophotocoagulation, as the total laser application duration was greater than 3 s per site, which is longer than the commonly used transscleral cyclophotocoagulation, despite not using a continuous motion and, therefore, the thermal effect was lower than with the traditional technique. Retreatments: the literature on retreatment is limited. The studies with the highest retreatment rates (≥20%) were those in which the delivered energies were modest (<100 J) (Tan et al 2010; Aquino et al 2015; Elheifney et al 2019; Nguyen et al 2019; de Crom et al 2020; Radhakrishnan et al 2020; Tekeli & Köse 2020) and/or the mean preoperative IOP was too high (>30 mmHg) to reach the success endpoint after a single session (Tan et al 2010; Aquino et al 2015; Elheifney et al 2019; Jammal et al 2019; Preda et al 2020; Tekeli & Köse 2020). Tekeli & Köse (2020) have found a significantly higher retreatment rate in eyes with other types of secondary glaucoma than in eyes with POAG and PXG.…”
Section: Mp‐tltmentioning
confidence: 99%
See 2 more Smart Citations
“…This method could have lead to cyclophotocoagulation, as the total laser application duration was greater than 3 s per site, which is longer than the commonly used transscleral cyclophotocoagulation, despite not using a continuous motion and, therefore, the thermal effect was lower than with the traditional technique. Retreatments: the literature on retreatment is limited. The studies with the highest retreatment rates (≥20%) were those in which the delivered energies were modest (<100 J) (Tan et al 2010; Aquino et al 2015; Elheifney et al 2019; Nguyen et al 2019; de Crom et al 2020; Radhakrishnan et al 2020; Tekeli & Köse 2020) and/or the mean preoperative IOP was too high (>30 mmHg) to reach the success endpoint after a single session (Tan et al 2010; Aquino et al 2015; Elheifney et al 2019; Jammal et al 2019; Preda et al 2020; Tekeli & Köse 2020). Tekeli & Köse (2020) have found a significantly higher retreatment rate in eyes with other types of secondary glaucoma than in eyes with POAG and PXG.…”
Section: Mp‐tltmentioning
confidence: 99%
“…Less severe complications have been described such as persistent mydriasis in 1.6% (Kaba et al 2020), 3% (Nguyen et al 2019), 5% (Magacho et al 2019), 11% (Radhakrishnan et al 2020) and 15% of cases (Magacho et al 2020). Asian race (OR: 13.5, p = 0.0131) and phakic status (OR: 3.1, p = 0.0386) are associated with higher odds of developing mydriasis (Radhakrishnan et al 2020).…”
Section: Mp‐tltmentioning
confidence: 99%
See 1 more Smart Citation
“…Dorairaj et al [56] identified that myopic females with brown irises were more likely to develop this complication. Radhakrishnan et al [57] reported higher odds of persistent mydriasis in those of Asian descent (odds ratio = 13.07, p < 0.001) and in phakic eyes (odds ratio = 3.12, p = 0.014). Causes of this condition may be multifactorial, while the most widely accepted mechanisms are the occlusion of iris vessels and iris ischemia secondary to an acute elevation in IOP leading to ischemic atrophy of the iris sphincter, with consequent pupil dilation [56].…”
Section: Discussionmentioning
confidence: 98%
“…This observation eventually resolved within one month. Postoperative reversible mydriasis has been described in several studies [39,41,[55][56][57]. Dorairaj et al [56] identified that myopic females with brown irises were more likely to develop this complication.…”
Section: Discussionmentioning
confidence: 99%